Contribuciones femeninas a la poesía guatemalteca: el siglo veinte - Frigerio, Franco Cerutti (2018)
This essay is a part of a larger research about Central American women writers during the XX Century up to the eighties. Guatemala is a nation where many women became outstanding poets; others were novelists and journalists; and many of them had a feminist position.